Perbandingan antara Model Pembelajaran Tugas Terstruktur dengan Tugas Mandiri Tidak Terstruktur terhadap Hasil Belajar Ekonomi - Zainal, Vetri Yanti (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2018)
Learning problems at Kasui 2 State Senior High School are currently a process of economic learning that is less than optimal so that learning outcomes in economic lessons are still low. The purpose of this study was to determine the comparison between structured task learning models with independent unstructured tasks on economic learning outcomes in the odd semester X students of Kasui Way 2 Public High School 2016/2017 Academic Year. The method used in this study is an experimental method, a population of 126 students consisting of 4 classes. Sample class X1 as experimental class 1 is 30 students and class X4 as experimental class 2 is 30 students. The sampling technique uses Cluster Random Sampling technique. The results of the study revealed that> tdaf, which is 4.55> 2.00 so it can be concluded that